Analisis Perbedaan Kinerja Keuangan Perusahan Sebelum dan Sesudah Akuisisi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2018 - Nurul Izza (CV. Publikasi Indonesia, 2022)
This research aims to be able to analyze the financial performance of the company before and after the acquisition of the company that made the acquisition. This research was conducted using descriptive quantitative methods by taking data from all companies that made acquisitions on the Indonesia Stock Exchange (IDX) with a time span between 2017-2018, Sampling in the study used purposive sampling methods, with data obtained by as many as 15 companies that made acquisitions. For normality tests using the Kolmogrov-Smirnov Test method and hypothesis tests using the Wilcoxon test. The results in this study showed that testing to financial ratios for the two years prior to acquisition and two years after acquisition did not increase significantly. This was reinforced by the results of the test using Wilcoxon's test of the company's financial performance before and after the acquisition in Current Ratio (CR), Quick Ratio (QR), Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Return On Assets (ROA), and Return On Equity (ROE) did not increase significantly.